Implementation of the Scaffolding Method in Improving Learning Outcomes with the Material of Respecting and Appreciating the Beliefs of Others at SD Negeri 095253 Talun Madear - Sriyani; Purba, Jamaluddin; Muliati; Lubis, Nining Indah Lestari (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the implementation of the scaffolding method in improving learning outcomes on the material